Adsorption of Organic Compounds in Leachate using Precipitated Calcium Carbonate (PCC) from Ale-Ale Shells - Yulistya Vidyaning Maulidya (Jurnal Sains dan Terapan Kimia, 2022)
Leachate waste from piles of garbage in the landfill (TPA) has a high concentration of Chemical Oxygen Demand (COD). High COD concentrations can cause a decrease in dissolved oxygen concentrations in the waters. Simple leachate treatment is carried out using the adsorption method with adsorbents derived from food waste. This research used Precipitated Calcium Carbonate (PCC) adsorbent from ale-ale shells. This study aims to evaluate the effect of particle size and calcination temperature variations on PCC yield and analyze the adsorption ability of PCC adsorbents in reducing COD concentrations. In addition, PCC was characterized using an infrared spectrophotometer (FTIR) and an X-ray diffractometer (XRD). Determination of COD concentration was carried out by permanganometric titration. The optimum PCC yield of 57.75% was obtained from Ale-ale shells with a particle size of 40 mesh with a calcination temperature of 800°C. The functional groups in PCC are C-O at wave numbers 1403 cm-1, 873 cm-1, and 713 cm-1. XRD characterization showed the presence of a calcite phase with a high peak intensity at 2 = 29.38°. The adsorption of organic matter on leachate by PCC (4.5 g/50 mL) with a stirring speed of 200 rpm for 240 minutes reduced the COD concentration of leachate from 1131.28 mg/L to 456.94 mg/L with an adsorption efficiency of 59.61%.